High-Growth Firms : Facts, Fiction, and Policy Options for Emerging Economies - Grover Goswami, Arti; Medvedev, Denis; Olafsen, Ellen (Washington, DC: World Bank, 2018)
Remarkably, a small fraction of firms account for most of the job and output creation in high-income and developing countries alike. Does this imply that the path to enabling more economic dynamism lies in selectively targeting high-potential firms? Or would pursuing broad-based reforms that minimize distortions be more effective? Inspired by these questions, this book presents new evidence on the incidence, characteristics, and drivers of high-growth firms based on in-depth studies of firm dynamics in Brazil, Côte d’Ivoire, Ethiopia, Hungary, India, Indonesia, Mexico, South Africa, Thailand, Tunisia, and Turkey. Its findings reveal that high-growth firms are not only powerful engines of job and output growth but also create positive spillovers for other businesses along the value chain. At the same time, the book debunks several myths about policies to support firm dynamism that focus on outward characteristics, such as firm size, sector, location, or past performance. Its findings show that most firms struggle to sustain rapid rates of expansion and that the relationship between high growth and productivity is often weak. Consequently, the book calls for a shift toward policies that improve the quality of firm growth by supporting innovation, managerial skills, and firms’ ability to leverage global linkages and agglomeration. To help policy makers structure policies that support firm growth, the book proposes a new ABC framework of growth entrepreneurship: improving Allocative efficiency, encouraging Business-tobusiness spillovers, and strengthening firm Capabilities. This book is the third volume of the World Bank Productivity Project, which seeks to bring frontier thinking on the measurement and determinants of productivity to global policy makers.